2017
DOI: 10.1016/j.ymthe.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from M1-Polarized Macrophages Potentiate the Cancer Vaccine by Creating a Pro-inflammatory Microenvironment in the Lymph Node

Abstract: Exosomes are small membrane-bound vesicular particles generated by most cells for intercellular communication and regulation. During biogenesis, specific lipids, RNAs, proteins, and carbohydrates are enriched and packaged into the vesicles so that the exosomal contents reflect not only the source but also the physiological conditions of the parental cells. These exosomes transport materials or signals to the target cells for diverse physiological purposes. Our study focused on the exosomes derived from M1-pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
223
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(228 citation statements)
references
References 32 publications
4
223
0
1
Order By: Relevance
“…Macrophages are a group of heterogeneous monocyte-macrophage lineage cells which play critical roles in innate immunity and also initiate the adaptive immune response. Macrophages display diverse phenotypes in response to different stimuli, and they are categorized into M1 and M2 subsets (Cheng et al, 2017). Cheng et al (2017) demonstrated that M1, rather than M2, macrophage-derived exosomes enhanced activity of lipid calcium phosphate nanoparticleencapsulated Trp2 vaccine and induced a stronger antigenspecific cytotoxic T cell response.…”
Section: Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are a group of heterogeneous monocyte-macrophage lineage cells which play critical roles in innate immunity and also initiate the adaptive immune response. Macrophages display diverse phenotypes in response to different stimuli, and they are categorized into M1 and M2 subsets (Cheng et al, 2017). Cheng et al (2017) demonstrated that M1, rather than M2, macrophage-derived exosomes enhanced activity of lipid calcium phosphate nanoparticleencapsulated Trp2 vaccine and induced a stronger antigenspecific cytotoxic T cell response.…”
Section: Macrophagesmentioning
confidence: 99%
“…Macrophages display diverse phenotypes in response to different stimuli, and they are categorized into M1 and M2 subsets (Cheng et al, 2017). Cheng et al (2017) demonstrated that M1, rather than M2, macrophage-derived exosomes enhanced activity of lipid calcium phosphate nanoparticleencapsulated Trp2 vaccine and induced a stronger antigenspecific cytotoxic T cell response. Moreover, EVs from macrophages are known to express functional immune modulating proteins including MHC class I and MHC class-II (Pitt et al, 2016), which preferentially induce Th1-type (cell-mediated) immune response that directs T cells to attack abnormal cells (such as cancer cells) or cells infected with intracellular parasites (Segura et al, 2005;Lynch et al, 2009;Yao et al, 2013).…”
Section: Macrophagesmentioning
confidence: 99%
“…For example, glypican‐1 containing exosomes are recognized as a biomarker for pancreatic cancer with absolute specificity and sensitivity . They can also serve as cancer vaccine adjuvant and nanocarriers for RNA interference and drug delivery . However, although exosomes are involved in every step of tumor metastasis, there still lack more explorations about underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…108 They can also serve as cancer vaccine adjuvant and nanocarriers for RNA interference and drug delivery. 109,110 However, although exosomes are involved in every step of tumor metastasis, there still lack more explorations about underlying mechanisms. Knowing more about these underlying mechanisms will provide new insight into cancer biology and even contribute to efficient prevention and therapeutic strategies for malignancies.…”
Section: Resultsmentioning
confidence: 99%
“…EV have been postulated to contribute to many physiological and pathological processes such as cancer progression, immune modulation, neurodegenerative diseases, or tissue regeneration (1,2,7,8). EV released from stem cells have been shown to modulate angiogenesis, prevent apoptosis or promote cell proliferation.…”
mentioning
confidence: 99%